HERPESVIRUS INFECTIONS AND CLINICAL-IMMUNOLOGIC INTERACTIONS IN PATIENTS WITH EARLY-ONSET ALZHEIMER’S DISEASE AND LATE-ONSET ALZHEIMER’S DISEASE - I. K. Malashenkova; D. P. Ogurtsov; S. A. Krynskiy; N. A. Khailov; N. D. Selezneva; Ya. B. Fedorova; E. V. Ponomareva; I. V. Kolykhalov; S. I. Gavrilova; N. A. Didkovsky (Медицинская иммунология, 2021)
Alzheimer’s disease (AD) is currently the most common cause of dementia. A significant role in the pathogenesis of AD belongs to the activation of the mechanisms of neuroinflammation. There is a hypothesis that chronic infections may play a role in the maintenance of the inflammatory response in AD. The aim of this work was to study the detection rate and DNA level of herpesviruses, as well as their possible relationship with the level of the key cytokines and with clinical parameters of AD in patients with early and late onset. 30 patients with AD and 33 healthy volunteers were enrolled. The quantitative determination of DNA of CMV, EBV, HHV-6, HHV-7 was carried out by PCR. The level of cytokines and soluble IL-1β antagonist (IL-1ra) in the blood was determined by ELISA. Herpesvirus infection with increased viral load was determined if at least one of the criteria was present: 1) DNA level of EBV and/or HHV-6 > 10,000 copies/ml in saliva; 2) presence of DNA of at least one of the EBV, HHV-6, HHV-7 viruses in the blood. In the subgroup of patients with early onset and increased viral load, there was a higher increase in the levels of a number of cytokines: proinflammatory IL-8 and IL-12, a Th2-cytokine IL-4, a cytokine of the adaptive immune response IL-2. However, the level of the anti-inflammatory protein IL-1ra was lower than in the controls. These changes may indicate a dysregulation of the antiviral response, with a predominance of activation of systemic inflammation and Th2-mediated reactions. Also, in early onset AD the increased viral load was associated with lower scores on Boston naming test. The results indicate that in studies of AD mechanisms and in the search for prognostic markers of the disease, it is important to take into account the heterogeneity of AD in terms of genetic predisposition factors, risk factors, immune parameters and clinical data. Such approach is necessary for the subsequent development of personalized approaches to the prevention and treatment of AD.